Social Pathology in Penyalin Cahaya Film: A Study of Sociology of Literature - Rusli, Herman; Mukhlis; Diba, Wulan Farah (Universitas Muhammadiyah Malang, 2024)
Social pathology often occurs in everyday life. Social pathology as a deviation of social behavior occurs due to various factors. These symptoms can arise from individual or group factors. Social deviations often also appear in literature and films. One of the films that most addresses social pathology is